KONTRIBUSI ARISAN DALAM MENAMBAH MODAL USAHA PERSPEKTIF EKONOMI ISLAM (Studi Kasus Pasar Pagi Desa Jagur Kecamatan Sambas) - Merly Merly (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The main problems in this study are (1) How is the contribution of arisan in increasing business capital in the Sambas morning market, Jagur Village, Sambas District, Sambas Regency? (2) What is the Islamic Economic Perspective on arisan activities in the Sambas morning market, Jagur Village, Sambas District, Sambas Regency? This type of research is qualitative research with the approach used is the (Field Research) approach. The sample of respondents in this study were 6 people consisting of one arisan leader and five arisan members. The data collection methods used were interviews, observations, and documentation. Furthermore, data processing and data analysis techniques were carried out to answer the existing questions. The data analysis includes data reduction, data display, and drawing conclusions. The results of this study indicate that the arisan carried out in the Sambas morning market, Jagur Village, Sambas District, Sambas Regency has a significant influence and contribution. This is because the funds obtained from the arisan activities are all used for productive needs or to increase business capital in order to make a profit. Then the arisan activity at the Sambas morning market, Jagur Village, Sambas District, Sambas Regency is one of the economic activities of the people that is institutionalized and popular. In the arisan system that is developing in society, especially traders, it is permitted in Islam. Because in the arisan carried out by traders there is no element of usury, fraud, because it is carried out fairly, transparently, witnessed by participants and no one is harmed. It is better in this study that traders who will participate in the arisan activity at the Sambas morning market, Jagur Village, Sambas District, Sambas Regency, are expected to pay attention to their ability to pay arisan contributions and to all arisan members at the Sambas morning market, Jagur Village, Sambas District, Sambas Regency, so that they are consistent in carrying out the arisan activities. Don't let there be arisan members who after receiving the arisan no longer want to participate in the arisan activities